PENERAPAN MODEL PEMBELAJARAN PDEODE UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF FISIKA SISWA KELAS XI IPA SMA NEGERI 1 RENGAT - Yusfa, Tria Del; ', Zulirfan; ', Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is aimed to find out the difference of cognitive ability of students class XI IPA at SMA Negeri 1 Rengat in learning physics between the class that is applying PDEODE learning and the class with conventional learning. Intact Group Comparison is used as the design of this research. The samples in this research are 76 students of class XI IPA SMA Negeri 1 Rengat and divided into experimental class and control class. The instrument in this research is a cognitive ability test consisting of 20 questions in categories C1 to C4. Data were analyzed using descriptive and inferential analysis. The result of this research shows that score of cognitive ability in implementation of PDEODE learning group is 78,55 in good category and in conventional learning group score of cognitive ability is 73,82 in good category. Based on the analysis of the data, it shows that the cognitive ability of the students in the experimental class is higher than the control class. The inferential analysis shows that there was a significant difference with t (74) = 2,495, p < 0,05 in 95% confidence interval of the difference. It can be concluded that learning PDEODE is better than conventional learning.